Amino acid stable carbon and nitrogen measurements for polar bear red blood cell, serum, and muscle tissue in the Beaufort Sea, 2008-2010 - John Whiteman; Merav Ben-David; Seth Newsome (Research Workspace)
These data are related to the physiological processes of fasting and feeding during natural, annual cycle of the polar bear. This project is important because it helps us understand the complete natural history of this species. Polar bears are unique in multiple ways, such as being the most carnivorous of the bear species, functioning as links between biological processes below and above the sea ice. Tissue samples were collected from polar bears in the Southern Beaufort Sea near the northern coast of Alaska from 2008-2010. Stable carbon and nitrogen isotope measurements were performed at the Center for Stable Isotopes at the University of New Mexico 2015-2017. Estimating the extent and timing of mortality caused by loss of energy reserves is a key component for understanding and predicting the effects of sea ice loss on bear survival. We found that throughout their annual cycle, polar bears in the Southern Beaufort Sea experience dynamic changes in the sources of carbon and nitrogen used for amino acid synthesis and protein maintenance. Data are presented as three csv files pertaining to red blood cells, serum, and muscle tissue: NPRB.project1513.RBCdata.csv NPRB.project1513.Muscledata.csv NPRB.project1513.Serumdata.csv